2015
DOI: 10.1123/jsep.2014-0203
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between the Coach-Created Motivational Climate and Athlete Engagement in Youth Sport

Abstract: Youth sport is a source of well-being for adolescents, yet experiences vary and attrition can be high. We sought to better understand the coach behaviors that foster positive experiences in youth sport by examining relationships between the motivational climate and athlete engagement (viz., confidence, dedication, enthusiasm, and vigor). We reasoned that a mastery climate (emphasis on effort and learning) would correspond with higher engagement, whereas a performance climate (emphasis on ability and outcome) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 22 publications
(20 reference statements)
6
60
0
4
Order By: Relevance
“…Other studies have shown that task orientation positively predicts autonomous Situational and Dispositional Factors 3 forms of motivation (intrinsic motivation and identified regulation) (e.g., Ntoumanis, 2001;Standage et al, 2003) and negatively predicts amotivation (e.g., Standage et al, 2003), whereas ego orientation is positively related with intrinsic motivation (e.g., Standage et al, 2003). In the sport context, positive relationship has been found between ego-involving climate and identified regulation (autonomous form of motivation) (Moreno et al, 2007), and proxy variables of autonomous motivation as dedication (Curran, Hill, Hall, & Jowett, 2015). Meanwhile, the task-involving climate was positively related to autonomous forms of motivation (Smith, Cumming, & Smoll, 2008), and proxy variables as dedication, enthusiasm (Curran et al, 2015), and enjoyment (Jaakkola, Ntoumanis, & Liukkonen, 2016).…”
Section: Situational and Dispositional Factors That Predict Motivatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that task orientation positively predicts autonomous Situational and Dispositional Factors 3 forms of motivation (intrinsic motivation and identified regulation) (e.g., Ntoumanis, 2001;Standage et al, 2003) and negatively predicts amotivation (e.g., Standage et al, 2003), whereas ego orientation is positively related with intrinsic motivation (e.g., Standage et al, 2003). In the sport context, positive relationship has been found between ego-involving climate and identified regulation (autonomous form of motivation) (Moreno et al, 2007), and proxy variables of autonomous motivation as dedication (Curran, Hill, Hall, & Jowett, 2015). Meanwhile, the task-involving climate was positively related to autonomous forms of motivation (Smith, Cumming, & Smoll, 2008), and proxy variables as dedication, enthusiasm (Curran et al, 2015), and enjoyment (Jaakkola, Ntoumanis, & Liukkonen, 2016).…”
Section: Situational and Dispositional Factors That Predict Motivatiomentioning
confidence: 99%
“…In the sport context, positive relationship has been found between ego-involving climate and identified regulation (autonomous form of motivation) (Moreno et al, 2007), and proxy variables of autonomous motivation as dedication (Curran, Hill, Hall, & Jowett, 2015). Meanwhile, the task-involving climate was positively related to autonomous forms of motivation (Smith, Cumming, & Smoll, 2008), and proxy variables as dedication, enthusiasm (Curran et al, 2015), and enjoyment (Jaakkola, Ntoumanis, & Liukkonen, 2016). Newton and Duda (1999) reported that sport research has traditionally used regression analysis to examine the interaction between goal orientations and motivational climates (at the individual level) and their further effects on behavioral variables.…”
Section: Situational and Dispositional Factors That Predict Motivatiomentioning
confidence: 99%
“…Sports coaches, for example, could ask questions that facilitate reflection on the youths' experiences and with that the sports coaches facilitate youth-driven learning (Super et al 2016). Within the role of sport as a safe haven, specific attention should be given to development of a safe and supportive context, where potential stressors for youth are minimised (Fraser-Thomas et al 2005, Curran et al 2015. Hence, depending on the needs and interests of socially vulnerable youths, sports activities can be adapted to support a specific role.…”
Section: Discussionmentioning
confidence: 99%
“…Sementara itu, motivational climate sangat berkembang pesat dalam pembahasan di konteks bidang olahraga. Kebanyakan penelitiannya membahas pengaruh motivational climate untuk meningkatkan motivasi intrinsik siswa di kelas olahraga, intensi, sikap, dan juga performa para (Atkins, Johnson, Force, & Petrie, 2015;Curran, Hill, Hall, & Jowett, 2015;Jõesaar, Hein, & Hagger, 2012;Smith, Smoll, & Cumming, 2007).…”
Section: Yaitu Ego-involving (Performance Climate) Dan Task Involvingunclassified